EVALUASI PENERAPAN PERATURAN DAERAH KABUPATEN BOJONEGORO NOMOR 13 TAHUN 2011 TENTANG PAJAK PARKIR DI RSUD KELAS B DR. R. SOSODORO DJATIKOESOEMO BOJONEGORO - VIKA SARI, NUR Vika (Jurnal Akuntansi AKUNESA, 2014)
Parking tax is a tax on the implementation of the road outside the park, either with the principal business and are provided as a daycare business, including the provision of a motor vehicle. The existence of a parking tax in Bojonegoro set in Bojonegoro District Regulation No. 13 of 2011, which in this regulation are the rates charged to the organizers of the road outside the park. With this regulation is expected actions related fraud parked outside the body can be minimized. Parking tax is a local tax levied as a source of revenue. This study used a descriptive-qualitative method, the data obtained are from interviews and secondary data obtained from previous studies, books and journals online. From the results of this data collection is then processed and analyzed to determine whether the parking at hospitals Class B Dr. R. Sosodoro Djatikoesoemo Bojonegoro are in accordance with the legislation in force. So that the results of the discussion can be concluded in order to answer the research question.Keywords: Bojonegoro District Regulation No. 13 of 2011, Parking tax.